THE INFLUENCE OF VOCABULARY AND GRAMMAR MASTERYON THE STUDENTS’ WRITING SKILL AT YOGYAKARTA STATE UNIVERSITY - Hastuti, Saptin Dwi Setyo (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2015)
This study aims to investigate the influence of (1) the students’ vocabulary mastery on their writing skill, (2) the students’ grammar mastery on their writing skill and(3) the students’ vocabulary and grammar mastery on their writing skill at Yogyakarta State University. This research was an ex-post facto. The population comprised the third semester students of Pendidikan Bahasa Inggris (PBI) study program at the Languages and Arts Faculty, Yogyakarta State University in the academic year 2013/2014. Therefore, this study showed that (1) vocabulary mastery positively influenced the students’ writing skill, (2) grammar mastery positively influenced the students’ writing skill, and (3) vocabulary and grammar mastery positively influenced the students’ writing skill. Keywords: vocabulary mastery, grammar mastery, and writing skill.